(untitled) (Jahangirnagar University Journal of Biological Sciences, 2025)
The soil physical and chemical properties (viz., moisture content, maximum water-holding capacity, pH, organic carbon, organic matter, nitrogen, phosphorus, potassium, calcium, magnesium, sulfur, zinc, copper, and manganese) of Bangabandhu Jamuna Eco-Park (BGEP), Sirajganj, Bangladesh was analyzed during 2021-2022. It was evident that the soils of the study area were slightly acidic in nature, where the pH values ranged from 5.88 to 6.69. The average moisture content and maximum water holding capacity of soils varied from 4.55% to 15.41% and 32.55% to 40.42%, respectively. The maximum moisture content 15.41% was recorded in Site D and the minimum value 4.55% was recorded in Site B, whereas the highest maximum water-holding capacity 40.42% was recorded in Site C and the lowest value 32.55% was recorded in Site B. The maximum organic carbon content of 2.41% was recorded at site D and the minimum value was 1.77% at Site B. The average values of nitrogen, phosphorus, potassium, calcium, magnesium, sulfur, zinc, copper, and manganese ranged from 0.09 to 0.12%, 7.01 to 8.20 μg/g, 0.13 to 0.17 meq/100g, 9.31 to 12.14 meq/100g, 1.27 to 1.94 meq/100g, 2.44 to 3.44 μg/g, 1.17 to 2.98 μg/g, 0.17 to 0.89 μg/g and 1.25 to 1.74 μg/g, respectively. The values of physical and chemical properties were also found to vary among surface (0-16 cm), sub-surface (17-32 cm) and substratum (33-48 cm) layers of soil. Significant correlation was found among the recorded soil parameters. A comprehensive finding of the current status of the physico-chemical attributes of soils in this important eco-park has been obtained, which will help in the eco-friendly management and development of this eco-park. Jahangirnagar University J. Biol. Sci. 13(1 & 2): 11-21, 2024 (June & December)